Two new names for extant Pteris species (Pteridaceae) - Kottaimuthu, Ramalingam; Dhasan, Nalluchamy Kamala; Basu, Muthuramalingam Jothi (Phytotaxa, 2020)
Pteris Linnaeus (1753: 1073) is the largest genus in Pteridaceae (PPG I 2016) and known to have 323 species globally (POWO 2020). It is a cosmopolitan genus with maximum diversity in tropical America, Africa and Asia but a few dwells in temperate regions too (Chao et al. 2014). The brake fern genus Pteris can be characterized from other members of Pteridaceae by its marginal indusiate sporangia borne continuously along most of the length of the pinnae from commissural veins and cingulate trilete spores (Prado & Windisch 2000).